Association of Ovarian Reserves with Body Mass Index, Age and Vitamin D in Infertile Females - Rijal, Hima; Koirala, Poonam (Journal of Institute of Medicine Nepal, 2023)
Introduction: Body mass index (BMI) may modulate ovarian reserve (OR) markers, and age-related fertility decline is well-established. Vitamin D has polygenetic effects on infertility, with its higher levels suggesting a positive correlation with OR markers. This study investigates the association of OR markers (AMH and FSH) with BMI, age and vitamin D in infertile females. Methodology: This is a retrospective study conducted at Tribhuvan University Teaching Hospital, Kathmandu, Nepal, over a period of one year. Serum level of FSH, LH, Estradiol, Thyroid Function Test, Testosterone, Prolactin and AMH levels were measured in all patients. Data records were collected and analysis was done. Body mass index, calculated as per Quetelet index, was also recorded. Results: The study includes 186 female patients with infertility, aged between 18 to 45 years. The mean body mass index (BMI) of the patients was 25.54 ± 4.55 kg/m2. The most common cause of infertility was unexplained (49.5%). No significant correlation between OR (AMH) and BMI (p = 0.92) or between OR(FSH) and BMI (p = 0.498) were noted. However, there was a significant negative correlation between age and BMI (p = 0.015), indicating that older patients had lower BMI values. There was also a significant negative correlation between age and OR (AMH) (p = 0.037), indicating that older patients had lower AMH levels. There was no significant correlation between age and OR (FSH) (p = 0.086). There was no significant correlation between vitamin D and OR(AMH) (p = 0.413) or between vitamin D and OR(FSH) (p = 0.868), indicating that vitamin D levels did not affect the ovarian reserve of the patients. Conclusions: OR markers showed no significant association with BMI, age, AMH, FSH, or vitamin D levels in infertile women.